PRECISION GNSS LANDING SYSTEM WITHOUT THE USAGE OF AUGMENTATION SYSTEMS - Bogunenko, Nikolay; Prygara, Oleksandr (Proceedings of National Aviation University (archive), 2014)
The article is devoted to the elaboration of a new ideological concept of the landing system which leads an aircraft during the approach and landing phases of a flight. The peculiarity of the system lies in the absence of an augmentation system which usually is used by all satellite landing systems known and operated today. The main benefits of the proposed GNSS landing system are its efficiency, integrity, low cost, sufficiently high reliability and safety.